Mobile 3D Secure Transmission Based on Anonymous Buyer-Seller Watermarking Protocol - Lee, Suk-Hwan; Kwon, Seong-Geun; Kwon, Ki-Ryong (Recent Advances in Communications and Networking Technology, 2014)
This paper presents a multiple-watermarking scheme for mobile 3D secure transmission. The proposed scheme embeds a unique watermark and a WCA (Watermark Certification Authority) watermark into the spatial and encryption domains of mobile 3D content based on the Anonymous Buyer-Seller Watermarking Protocol. The seller generates a unique watermark and embeds it into the distribution of vertex data of the 3D content object. After receiving the encrypted watermark from the WCA, the seller embeds it into the encrypted vertex data by using an operator that satisfies the privacy homomorphic property. The proposed method was implemented using the mobile content tool, PowerVR MBX. Experimental results verified that the proposed method was capable of copyright protection and preventing illegal copying. The latter was verified by the watermarks being accurately extracted in the case of geometrical attacks.
Keywords: Mobile watermarking protocol